Searching for soul: work and human evolution - Krahnke, Keiko, author; Geroy, Gary D., advisor; Banning, James H., committee member; Boyd, James, committee member; Feller, Richard, committee member (Colorado State University. Libraries, 1999)
A grounded theory study reveals that when nine key concepts are present, workers find the optimal meaning of work. The concepts provide the constructs for the emergent work and human evolution theory. The theory is: "For work to be meaningful to the individuals, it must provide a framework where people with different backgrounds and needs can choose to grow physically, mentally, emotionally, and spiritually at our own speed and will, experiment and discover our essence, manifest our vision in a concrete practical manner, be of service to others, and be purposeful by doing something we enjoy in the world with both visible and invisible guidance." When an organization understands the relationship between work and human evolution, it becomes critical to reconceptualize the organizational view of work and people. The reconceptualization is critical in meeting the challenges of the coming era.
Keywords: vocational education; philosophy; theory; evolution